Apply the quotient rule, which is:
dxdg(x)f(x)=g2(x)−f(x)dxdg(x)+g(x)dxdf(x)
f(x)=axsin(3x) and g(x)=3.
To find dxdf(x):
-
The derivative of a constant times a function is the constant times the derivative of the function.
-
Apply the product rule:
dxdf(x)g(x)=f(x)dxdg(x)+g(x)dxdf(x)
f(x)=x; to find dxdf(x):
-
Apply the power rule: x goes to 1
g(x)=sin(3x); to find dxdg(x):
-
Let u=3x.
-
The derivative of sine is cosine:
dudsin(u)=cos(u)
-
Then, apply the chain rule. Multiply by dxd3x:
-
The derivative of a constant times a function is the constant times the derivative of the function.
-
Apply the power rule: x goes to 1
So, the result is: 31
The result of the chain rule is:
3cos(3x)
The result is: 3xcos(3x)+sin(3x)
So, the result is: a(3xcos(3x)+sin(3x))
To find dxdg(x):
-
The derivative of the constant 3 is zero.
Now plug in to the quotient rule:
3a(3xcos(3x)+sin(3x))